Best Answer

the general form of quadratic equation is ax^2+bx+c therefore the formula for factorisation is =-b+(or)-sqrt(b^2-4ac)/2a on applying this formula we get the roots as:1/2+(or)-sqrt(5)/2

More answers

2(x - 1)(x + 1)

Q: How do you factor 2x squared minus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2(x^2 - 8)

(x - 2)(2x + 7)

(2x - 9)(2x - 9) or (2x - 9)2

(x + 3)(3x - 2)

Factor out a 22(X2 + X - 12)2(X - 3)(X + 4)===========

Related questions

(x - 2)(2x + 3)

x(3x - 2)

x(x - 2)

2(x^2 - 8)

(2x - 3)(x + 2)

(x - 2)(2x + 7)

(x + 2)(x - 4)

(x - 2)(2x - 3)

(2x - 9)(2x - 9) or (2x - 9)2

2(x + 7)(x - 7)

(x + 3)(3x - 2)

10x^2 - x - 2 = (5x + 2)(2x - 1)